Analisis Social Media Marketing Terhadap Minat Menggunakan Aplikasi Pesan Antar Makanan Melalui Brand Awareness Sebagai Variabel Mediasi - Adistia; Asep Muhamad Ramdan; Sopyan Saori (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
By utilizing social media, it will make it easier for a company to market its products (social media marketing), so this must be considered by every food delivery application because good social media marketing will increase brand awareness to the audience so as to create purchase intention. The purpose of this study was to determine the effect of brand awareness in mediating the relationship between social media marketing on purchase intention. The method used in this research is quantitative method with descriptive and verification approaches. The population in this study were @shopeefood_id Instagram followers. The sample of this study amounted to 200 respondents who were then analyzed using SEM (Structural Equation Modeling) techniques with the help of AMOS version 22. The results of data processing show that social media marketing has a significant effect on brand awareness. Brand awareness has a significant effect on purchase intention with value. And brand awareness successfully mediates the relationship between social media marketing on repurchase intention on Instagram followers @shopeefood_id.